+0  
 
0
118
1
avatar+55 

help 

 Oct 18, 2018

Best Answer 

 #1
avatar
0

Expand the following:
(2 x + 1) (x - 2) (x + 3)

Multiply x - 2 and x + 3 together using FOIL.
(x - 2) (x + 3) = (x) (x) + (x) (3) + (-2) (x) + (-2) (3) = x^2 + 3 x - 2 x - 6 = x^2 + x - 6:
x^2 + x - 6 (2 x + 1)

Multiply out (2 x + 1) (x^2 + x - 6).

2x^3 + 3x^2 - 11x - 6

 Oct 18, 2018
 #1
avatar
0
Best Answer

Expand the following:
(2 x + 1) (x - 2) (x + 3)

Multiply x - 2 and x + 3 together using FOIL.
(x - 2) (x + 3) = (x) (x) + (x) (3) + (-2) (x) + (-2) (3) = x^2 + 3 x - 2 x - 6 = x^2 + x - 6:
x^2 + x - 6 (2 x + 1)

Multiply out (2 x + 1) (x^2 + x - 6).

2x^3 + 3x^2 - 11x - 6

Guest Oct 18, 2018

24 Online Users

avatar
avatar
avatar
avatar